Urinary stones as a novel matrix for human biomonitoring of toxic and essential elements - Kuta, J; Smetanová, S; Benová, D; Kořistková, T; Machát, J (Environmental geochemistry and health, 2016)
Monitoring of body burden of toxic elements is usually based on analysis of concentration of particular elements in blood, urine and/or hair. Analysis of these matrices, however, predominantly reflects short- or medium-term exposure to trace elements or pollutants. In this work, urinary stones were investigated as a matrix for monitoring long-term exposure to toxic and essential elements. A total of 431 samples of urinary calculi were subjected to mineralogical and elemental analysis by infrared spectroscopy and inductively coupled plasma mass spectrometry. The effect of mineralogical composition of the stones and other parameters such as sex, age and geographical location on contents of trace and minor elements is presented. Our results demonstrate the applicability of such approach and confirm that the analysis of urinary calculi can be helpful in providing complementary information on human exposure to trace metals and their excretion. Analysis of whewellite stones (calcium oxalate monohydrate) with content of phosphorus <0.6 % has been proved to be a promising tool for biomonitoring of trace and minor elements.
Keywords: Urinary stones; Environmental Monitoring; Urolithiasis; Male; Calcium Oxalate; zeměpis; stopové prvky; monitorování životního prostředí; sexuální faktory; Česká republika; Adult; Age Factors; Aged; dospělí; mužské pohlaví; senioři; Biomonitoring; Geography; Urinary Calculi; Czech Republic; močové kameny; senioři nad 80 let; lidé; Trace elements; ženské pohlaví; Exposure; Humans; Sex Factors; věkové faktory; Aged, 80 and over; šťavelan vápenatý; Trace Elements; Female; lidé středního věku; Middle Aged